How weather conditions affect well-being: an explanation from the perspective of environmental psychology - Weida Zhang; Wenzhang Li (Frontiers in Public Health)
Currently, the issue of how weather conditions influence well-being has garnered widespread attention from researchers, and the rise of environmental psychology has provided a novel theoretical framework and quantitative analytical tools for understanding the relationship between the two. Through a review of domestic and international literature, this paper reveals the complex and interactive relationship between weather conditions and well-being. Firstly, weather conditions, as an important component of the natural environment, encompass multiple dimensions such as light, temperature, precipitation, humidity, wind speed, air quality, and extreme weather events. These factors not only directly influence various dimensions of well-being but may also interact to form cumulative effects that collectively shape an individual’s well-being experience. Secondly, weather conditions indirectly affect well-being levels by influencing an individual’s physiological state, emotional mood, and patterns of social interaction. This paper provides a thorough review of the theoretical basis, empirical evidence, and physiological mechanisms of how weather impacts well-being, offering theoretical references for enhancing individual well-being and suggesting directions for future research.